Monitoring of optimized SERS active gel substrates for painting and paper substrates by unilateral NMR profilometry1. (20th July 2014) - Doherty, Brenda; Presciutti, Federica; Sgamellotti, Antonio; Brunetti, Brunetto G.; Miliani, Costanza; Ropret, Polonca; Madariaga, Juan Manuel
<x xml:space="preserve">Abstract</x> In order to realize a surface enhanced Raman spectroscopy (SERS) gel protocol with portable Raman instrumentation, this contribution oversees the optimization of a removable SERS active methylcellulose gel and the applicability of an innovative gelatin substrate. Analytical evaluations by non‐invasive portable nuclear magnetic resonance (NMR) profilometry with regards to methylcellulose and gelatin film penetration and removal from an unvarnished painted surface and commercial dyed paper substrates have been carried out, respectively, following successful SERS measurements. Both gels have been specifically prepared in accordance to the substrate under exam so as to simultaneously permit sufficient surface interaction for Raman enhancements to be recorded with limited penetration into or subsequent damage on removal of the matrix under study. This work continues to bridge the gap towards non‐invasive SERS measurements and in‐situ SERS measurements. Copyright © 2014 John Wiley & Sons, Ltd.